WAKAF DAN PENDIDIKAN ISLAM KLASIK - Sihaloho ‎, Wardani (UIN Sumatera Utara Medan, 2024)
This article discusses the role of waqf in the development of Islamic education during the classical era. Waqf, as an Islamic philanthropic instrument, served as a crucial foundation for building educational institutions such as madrasas, libraries, and universities in the Islamic world. During the golden age of Islamic civilization, waqf not only provided high-quality educational facilities but also ensured the sustainability of learning and the dissemination of knowledge. The contribution of waqf enabled the spread of religious sciences, philosophy, science, and various other disciplines, fostering a rich and enduring intellectual tradition. This article examines how the management and utilization of waqf influenced the quality and sustainability of education during that era, as well as its impact on society at large. The study highlights the importance of revitalizing the concept of waqf to support modern, inclusive, and sustainable education.Keywords: waqf, classical Islamic, and Islamic civilization.